1950
DOI: 10.2514/8.1656
|View full text |Cite
|
Sign up to set email alerts
|

On Plastic Buckling of a Compressed Strip

Abstract: A n ACpl -At P 2 = cos L vi + «i J ^ (i _ k) vm J-^v This is in agreement with the solution obtained by Evvard. 5 SUMMARY Three types of edges can border a region: (1) a leading edge, (2) a trailing edge, and (3) an edge bordering another region. For types (2) and (3) the method given in references 2 and 3 applies, without regard to the homogeneous solution to the integral equation. For type (1) an additional analysis similar to that given here must be used. restated the inconsistency of deformation theories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1953
1953
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Neale (1974) estimated the plastic buckling of cylinders subjected to torsion using the flow theory of plasticity in the presence of imperfections and found that the critical torsional stress was reduced by extremely small and unavoidable imperfections, but that it was not sensitive to the magnitude of imperfections. Cicala (1950) concluded in his approximate analysis of strips that small imperfections in the specimen would reduce the bifurcation load predicted by flow theory to the level of the deformation theory. Hutchinson (1972) investigated the imperfection sensitivity of spherical shells subjected to external pressure in the plastic range.…”
Section: Considerations On the Initial Imperfectionsmentioning
confidence: 99%
“…Neale (1974) estimated the plastic buckling of cylinders subjected to torsion using the flow theory of plasticity in the presence of imperfections and found that the critical torsional stress was reduced by extremely small and unavoidable imperfections, but that it was not sensitive to the magnitude of imperfections. Cicala (1950) concluded in his approximate analysis of strips that small imperfections in the specimen would reduce the bifurcation load predicted by flow theory to the level of the deformation theory. Hutchinson (1972) investigated the imperfection sensitivity of spherical shells subjected to external pressure in the plastic range.…”
Section: Considerations On the Initial Imperfectionsmentioning
confidence: 99%